Children's services in the age of information technology: What matters most to frontline professionals. (November 2019) - Sarwar, Atif; Harris, Martin
Summary: The last two decades have seen information systems featuring prominently in calls for the modernisation of the UK social care system. However, critics have maintained that these systems are of limited value to social care professionals whose design and implementation is driven by a preoccupation with performance management and a culture of professional audit and accountability, precepts of 'managerialism'. However, this area of research has often suffered from lack of focus on how technological changes affect public administration and service delivery and often characterises technology as a politically neutral tool detached from its socio-political context whilst also ignoring the strategic predispositions of human service professionals. Findings: This research was conducted in three local authorities in England. Using the 'technological affordance' perspective, we contend that the way social workers interact with Integrated Children's System is shaped by the discord between socio-historically evolved professional values epitomising the social work profession and managerialist reforms promoting standardised ways of performing it. Application: Integrated Children's System has transformed social work from an art to a technical activity, dominated by unimaginative and routinised working practices. Social workers are becoming peripheral figures and this is where social work needs to be reclaimed. Policymakers need to rethink taken for granted assumptions that practitioners would replace their professional expertise with technology and realise that the effective use of Integrated Children's System depends on bureau-professionalised judgements of social workers. Whilst specific patterns of technology usage can be developed and institutionalised, real objectives of children's social services should not be sacrificed.